Quality of Life Indicators for Adolescent with Diabetes Type1 - Ayadi, Rima; Abidi, Sana (Milev Journal of Research and Studies, 2021)
This study aims to reveal some indicators of the quality of life of adolescents with diabetes through the four main dimensions of the quality of life, which are: health-related quality of life, psychological quality of life, social quality of life, and environmental quality of life. The study sample consisted of 10 adolescents with type 1 diabetes, 05 of whom were males and 05 were females. We relied on the descriptive analytical approach along with the method of content analysis. The results of the study concluded: - The presence of positive indicators in adolescents with diabetes within the four dimensions of quality of life: optimism, satisfaction, acceptance of disease, sense of activity and ability to perform duties, and access to appropriate health services. - The presence of negative indicators in adolescents with diabetes within the four dimensions of quality of life: a sense of anxiety and depression, low self-esteem, a sense of fatigue and poor relationships with peers -Kolar ,kathryn, &Rassner. (1996). quality of life in youth with insulin -depandent diabetes mellitis.Dessertation abstracts international, p. 6178. -Krishnavathana, h., W Loar, R., J Anderson, B., & A Heptulla, R. (2006). the role of socioeconomic status, depression,quality of life ,and glycemic contril in type1 diabetes mellitus. journal of pediatrics-elsevier. -Odell, M., &Delors, A. (1997). therolatioship between social and adjustement in adolescents with diabtes. dissertation abstracts international, p. 2693. -Wherrett, D., Huot, C., Mitchell, B., &Pacaud, D. (2013). le diabète de type1 chez les enfants et les adolescents. canadian journal of diabetes, pp. 5531-5541